Listening, dialogue, and change: The role of dialogic feedback in shaping future teachers in Bedouin society - Abu-gweder, Aref (Journal of Interdisciplinary Studies in Education, 2026)
This study investigates how dialogic feedback shapes professional identity, agency, and reflective practice among Arab-Bedouin female pre-service teachers in southern Israel. Using a qualitative interpretive design, 12 participants engaged in semi-structured interviews to explore their experiences with culturally mediated mentoring during practical teacher training. Thematic analysis revealed that mentors acted as cultural mediators, facilitating dialogue that balanced respect for traditional norms with opportunities for critical reflection. Dialogic feedback emerged as a space for professional identity development, enabling participants to integrate inherited cultural values with contemporary pedagogical practices. Moreover, it fostered agency, empowering student teachers to take ownership of their learning, contribute ideas, and exercise leadership in classroom decision-making. A reciprocal dimension was also identified, wherein mentors experienced professional growth and reflective renewal through the feedback process. Cultural challenges, including hierarchical social norms and concerns about respect, highlighted the necessity of culturally responsive strategies to ensure meaningful participation. Overall, the findings demonstrate that dialogic feedback operates as a relational, contextually sensitive mechanism that simultaneously supports professional development, reflective learning, and the co-construction of a learning community.